Authentic Leadership’s Environmental Impact: Empowering Employee Engagement and Sustainability - Younas, Sohail; Waheed, Nabeel Abdul; Hafeez, Nauman; Mirza, Farhan (Pakistan Journal of Humanities and Social Sciences, 2023)
Organisational issues, wrongdoings of employees and a sense of security are integral issues that need to be addressed. Leaders of the corporate world must understand how to make an environment where employees can feel friendly and inform the managers about wrongdoings. The aim of study is to explore the impact of authentic leadership, Psychological safety on whistle-blowing with mediating mechanism of collectivism. Data were obtained from 380 respondents from the telecommunication sector of Pakistan. Results show that the significant relations between variables and collectivism partially mediate between relationships. The study has some limitations that need to be avoided by future researchers. Leaders can use the study by applying the results to improve organisational performance.